2023
DOI: 10.1111/dom.14999
|View full text |Cite
|
Sign up to set email alerts
|

Effects of finerenone in people with chronic kidney disease and type 2 diabetes are independent of HbA1c at baseline, HbA1c variability, diabetes duration and insulin use at baseline

Abstract: Aim: To evaluate the effect of finerenone by baseline HbA1c, HbA1c variability, diabetes duration and baseline insulin use on cardiorenal outcomes and diabetes progression. Materials and Methods: Composite efficacy outcomes included cardiovascular (cardiovascular death, non-fatal myocardial infarction, non-fatal stroke or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…The FIDELITY prespecified pooled analysis of both Phase 3 studies confirmed a significant relative risk reduction of 23% in the composite kidney endpoint with finerenone versus placebo, and of 14% in the composite cardiovascular endpoint, including a 22% relative risk reduction in HF‐related hospitalization 67 . Post‐hoc analyses showed that the efficacy of finerenone was not modified by baseline HbA1c, HbA1c variability, diabetes duration, baseline insulin use, or obesity 68,69 . Finerenone was well tolerated, with AEs, kidney‐related AEs, and serious AEs occurring at similar rates to placebo 67 .…”
Section: Clinical Evidence For Non‐steroidal Mineralocorticoid Recept...mentioning
confidence: 89%
See 1 more Smart Citation
“…The FIDELITY prespecified pooled analysis of both Phase 3 studies confirmed a significant relative risk reduction of 23% in the composite kidney endpoint with finerenone versus placebo, and of 14% in the composite cardiovascular endpoint, including a 22% relative risk reduction in HF‐related hospitalization 67 . Post‐hoc analyses showed that the efficacy of finerenone was not modified by baseline HbA1c, HbA1c variability, diabetes duration, baseline insulin use, or obesity 68,69 . Finerenone was well tolerated, with AEs, kidney‐related AEs, and serious AEs occurring at similar rates to placebo 67 .…”
Section: Clinical Evidence For Non‐steroidal Mineralocorticoid Recept...mentioning
confidence: 89%
“…67 Post-hoc analyses showed that the efficacy of finerenone was not modified by baseline HbA1c, HbA1c variability, diabetes duration, baseline insulin use, or obesity. 68,69 Finerenone was well tolerated, with AEs, kidney-related AEs, and serious AEs occurring at similar rates to placebo. 67 Hyperkalaemia was confirmed as the most notable treatment-related AE associated with finerenone (14% of patients), but the rate of hyperkalaemia-related discontinuation was relatively low (1.7%), indicating that it was manageable through serum potassium monitoring and dose adjustments.…”
Section: Finerenone Phase 3 Trialsmentioning
confidence: 92%
“…The FIDELITY study, which combined the FIGARO-DKD and FIDELIO-DKD studies, demonstrated an average of 36% reduction in UACR at 4 months and a significant reduction in the combined renal outcome (renal failure, >57% eGFR reduction, and renal disease-related death) (HR 0.77, p = 0.0002) [170]. The benefit on cardiorenal outcome was observed irrespective of the use of SGLT2is, glycemic control, and duration of diabetes in the FIDELITY cohort [171,172].…”
Section: Finerenonementioning
confidence: 96%
“…Furthermore, some FIDELITY analyses emphasize the benefits of early treatment initiation and co-administration of potassium-binding agents to maximize the protective effects of FIN in individuals with DKD ( 100 , 103 ). FIN improved cardiorenal outcome in patients with DKD, regardless of baseline HbA1c ( 94 , 104 , 105 ), HbA1c variability ( 104 ), diabetes duration ( 104 ), baseline insulin use ( 104 , 105 ), baseline HF history ( 106 , 107 ), prevalent atherosclerotic CVD ( 108 ), and history of atrial fibrillation/flutter at baseline ( 96 ). Additionally, it is worth noting that the antihypertensive effect of adding FIN to a maximally tolerated dose of ACEI or ARB was relatively modest ( 87 , 88 ).…”
Section: Renal Protection Of Fin In Clinicmentioning
confidence: 99%